2020
DOI: 10.1007/s11192-020-03454-0
|View full text |Cite
|
Sign up to set email alerts
|

A two-dimensional bibliometric index reflecting both quality and quantity

Abstract: We propose a two-dimensional bibliometric index that strikes a balance between quantity (as measured by the number of publications of a researcher) and quality (as measured by the number of citations to those publications). While the square of h-index is determined by the maximum area square that fits under the citation curve of an author when plotting the number of citations in decreasing order, the rec-index is determined by the maximum area rectangle that fits under the curve. In this context we may disting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The literature on measuring research productivity has addressed the subject at two levels (at individual researcher or institution level), and can be generally divided into two main categories: (1) research studies that empirically measured productivity (at individual or institution level) in different contexts (research fields, specializations, countries, periods) using existing indexes or indicators such as h-index, total citations, total publications or author position (Kaba, 2020; Lund, 2019; Pratikno, 2018; Darmadji et al , 2018; Hu et al , 2018; Lowry et al , 2007). (2) Research studies that developed new metrics/indices and models for measuring productivity at the individual level (Silva et al , 2015; Dev et al , 2015; Caminiti et al , 2015; Akbaritabar et al , 2018; Levene et al , 2020; Tuan et al , 2020) or at the institution level (Huang, 2012; Sahoo et al , 2016). However, in general, there are limited research articles that have developed new metrics to measure research productivity at the university/institution level, where searching in Scopus database for recent articles on this subject produces limited results.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on measuring research productivity has addressed the subject at two levels (at individual researcher or institution level), and can be generally divided into two main categories: (1) research studies that empirically measured productivity (at individual or institution level) in different contexts (research fields, specializations, countries, periods) using existing indexes or indicators such as h-index, total citations, total publications or author position (Kaba, 2020; Lund, 2019; Pratikno, 2018; Darmadji et al , 2018; Hu et al , 2018; Lowry et al , 2007). (2) Research studies that developed new metrics/indices and models for measuring productivity at the individual level (Silva et al , 2015; Dev et al , 2015; Caminiti et al , 2015; Akbaritabar et al , 2018; Levene et al , 2020; Tuan et al , 2020) or at the institution level (Huang, 2012; Sahoo et al , 2016). However, in general, there are limited research articles that have developed new metrics to measure research productivity at the university/institution level, where searching in Scopus database for recent articles on this subject produces limited results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many prior attempts have suggested metrics/indexes for measuring research productivity, as will be shown in the literature review. Most previous and existing methods for measuring research productivity have included an assessment of the research’s impact using a citations indicator (Kaba, 2020; Levene et al , 2020; Sahoo et al , 2016; Dev et al , 2015; Huang, 2012). However, productivity is not adequately evaluated this way.…”
Section: Introductionmentioning
confidence: 99%
“…The linear application of citations when comparing different fields of research demonstrates some of its possible limits; since fields with a greater number of researchers invariably lead to a greater number of citations and a higher impact index of the journals in the categories related to those fields. Several methods have been proposed to normalize these bibliometric indicators [8], [9]. However, depending on the academic discipline under study, other dissemination channels may be more relevant and consequently must also be considered, such as book chapters and aspects related to knowledge transfer, such as patents and spin-offs.…”
Section: Introductionmentioning
confidence: 99%